The The Effect Of Earnings Management On Financial Distress With Leverage As A Moderating Variable - Aisah; Fauziyah; Ahmad Yani (LP2M IAIN Palopo, 2026)
The purpose of this study is to examine how leverage functions as a moderating variable in energy sector corporations between 2021 and 2024, as well as how earnings management affects financial distress. The urgency of this research stems from the significant volatility of the energy sector, which exposes enterprises to fluctuating cash flows, increasing financial strain and elevating the risk of financial distress, particularly in the post-pandemic period. This study employs a quantitative methodology with a causal-associative design, utilizing secondary data from the annual reports of companies listed on the Indonesia Stock Exchange. Purposive sampling was used to obtain 148 firm-year observations. The data were analyzed using multiple regression, simple linear regression, and moderated regression analysis (MRA). The results show that earnings management has a significant negative effect on financial distress, indicating that effective earnings management practices reduce the likelihood of financial distress. However, leverage is found to have no significant effect on financial distress, suggesting that the stable cash flows and strong asset structures of energy companies enable them to manage their debt levels effectively. Additionally, leverage does not moderate the relationship between earnings management and financial distress. These findings indicate that, in the energy sector, earnings management plays a more important role than leverage in reducing financial distress.